The Plebeian Republic. The Huanta Rebellion and the Making of the Peruvian State, 1820-1850. / Cecilia Méndez Gastelumendi. Durham: Duke University Press, 2005, XVI + 343 pp. - Pereyra Chávez, Nelson E. (2006)
Esta reseña no presenta resumen.